Transforming Literacy and Social Skills through Storytelling in a Community-Based Setting - Nurhidayati, Alfidah Rahmasari; Yasmin, Nabila (Journal La Edusci, 2024)
The research question of this study evaluates the impact that the storytelling tradition at Rumah Baca Rambutan has on children concerning literacy, emotions, social skills, and creativity. Through the qualitative case study, the study discovers that storytelling enhanced the children’s reading appreciation, language, and literacy learning as well as culture. Emotional literacy interconnection was also achieved through the use of storytelling since learners developed empathy and social relationships with characters. In addition, storytelling can develop creative thinking and imagination, through which children can act as main constructors of narratives what would support their cognitive flexibility and problem solving. Notably, the study enjoys the use of storytelling in the passing of cultural values of a certain group besides enhancing the sense of belonging in children. The study contributes to the knowledge that informal narrative intervention enhancing formal and community learning can promote literacy, well-being, and cultural identity when implemented in low and rural context, such as Indonesia. Implications of these outcomes for reform in education include the need to embrace cultural production approaches that are educationally relevant so as to facilitate consideration of children’s developmental experiences.